2019
DOI: 10.21203/rs.2.15975/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Birth outcomes in a Swedish population of women reporting a history of violence including domestic violence during pregnancy: A longitudinal cohort study

Abstract: Background: Victimisation of women is encountered in all countries across the world, it damages the mental and physical health of women. During pregnancy and the postpartum period, women are at a greater risk of experiencing violence from an intimate partner. The aim of this study was to explore childbirth outcomes in a Swedish population of women reporting a history of violence including domestic violence during pregnancy. Methods: A longitudinal cohort design was utilised. In total 1939 pregnant women ≥ 18 y… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…Asimismo, se ha reportado que las gestantes adolescentes comprometidas tempranamente son las más dependientes de sus parejas, lo que las hace más vulnerables a los abusos 7 . No obstante, se sabe que estos porcentajes pueden variar según cada realidad; por ejemplo, estudios realizados en Etiopía y Suecia reportaron que la prevalencia de violencia en gestantes fue del 31% y el 2%, respectivamente, pero ambos destacan el hecho de que cuanto más jóvenes eran las gestantes más grave era el maltrato 17,18 . La variación entre nuestros resultados y los de otros estudios podría atribuirse a las distintas medidas para evaluar la exposición a la violencia y a las diferencias étnicas y socioeconómicas de todas las poblaciones.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Asimismo, se ha reportado que las gestantes adolescentes comprometidas tempranamente son las más dependientes de sus parejas, lo que las hace más vulnerables a los abusos 7 . No obstante, se sabe que estos porcentajes pueden variar según cada realidad; por ejemplo, estudios realizados en Etiopía y Suecia reportaron que la prevalencia de violencia en gestantes fue del 31% y el 2%, respectivamente, pero ambos destacan el hecho de que cuanto más jóvenes eran las gestantes más grave era el maltrato 17,18 . La variación entre nuestros resultados y los de otros estudios podría atribuirse a las distintas medidas para evaluar la exposición a la violencia y a las diferencias étnicas y socioeconómicas de todas las poblaciones.…”
Section: Discussionunclassified
“…Este resultado ha sido previamente reportado por un metaanálisis que encontró que las mujeres que experimentan violencia durante el embarazo (por parte de su pareja íntima) tienen un mayor riesgo de tener un resultado adverso en el parto, en comparación con las mujeres que no experimentan esta situación, lo que obliga a tener ingresos repetitivos al hospital 22 . Del mismo modo, otro estudio reportó que las gestantes que experimentaron violencia doméstica durante el embarazo tuvieron un alto riesgo de tener un parto por cesárea planificada o por emergencia (OR: 1,50; IC95%: 1,09-2,06) 17 .…”
Section: Discussionunclassified
“…Spontaneous labor (as opposed to induction and a vaginal birth) was less prevalent in the "emotionally unhealthy" group while there was a higher prevalence in the "emotionally unhealthy" group in the use of epidural analgesia or augmentation of labor and babies born to have a severe neonatal diagnosis. [34,35,37,39,46,53,56,73] did not report EPDS scores while seven studies [35,37,39,44,56,70,73] did not provide measures of SOC. Not surprisingly, none of the seven studies [35,37,39,44,56,70,73] reported relationship between EPDS and SOC measures.…”
Section: Relationship Of Pro With Socmentioning
confidence: 99%
“…1 This definition is consistent with the description provided by the World Health Organization [WHO] (2013). Existing literature well documents the adverse impact of DFV during and around pregnancy on mental health and well‐being of victims (Finnbogadóttir et al, 2020; Tavoli et al, 2016). As a result, interventions aiming to improve psychosocial outcomes of DFV victims have been increasing, albeit with continuing methodological limitations and mixed findings (Daley et al, 2020; Sapkota et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%